Securing the Future of Digital Health: How Hospitals Protect AI Systems from Cyber Breaches - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Securing the Future of Digital Health: How Hospitals Protect AI Systems from Cyber Breaches The integration of Artificial Intelligence (AI) into healthc...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care